Pharmaceutical ethnobotany in the Mahabad (West Azerbaijan) biosphere reserve: ethno-pharmaceutical formulations, nutraceutical uses and quantitative aspects - Jafarirad, Saeed; Rasoulpour, Ibrahim (Brazilian Journal of Pharmaceutical Sciences, 2019)
This study endeavors to overcome the limits of an orally transmitted pharmacopoeia, and tries to utilize the large ethnobotany patrimony of the area to investigate the biological diversity. Thirty-five traditional practitioners from dissimilar ethnic groups including traditional health practitioners (THPs) and indigenous people were interviewed. A total of 35 species of plants, belonging to 20 families were recognized for the treatment of more than 26 types of ailments. Informant consensus factor (FIC) values of this study reflected the high agreement in the use of plants in the treatment of gastro-intestinal complaints, infectious, parasitic diseases and constipation among the informants. Constipation had the highest use-reports and 8 species of plants had the highest fidelity level (FL) of 100%. In addition one of the species showed the highest relative importance (RI) value of 2.00. Priority should be given to phytochemical investigation of plants that scored the highest FL, FIC, RI values; as such values could be considered as a good indicator of potential plants for discovering new drugs. In addition, traditional knowledge of THPs should be taken into consideration in order to smooth continuation and extension of the nutraceutical aspects and biological diversity of the region.